Service quality dimensions and customer satisfaction: empirical evidence from retail banking sector in Oman. (17th November 2019) - S., Ananda; Devesh, Sonal
Abstract : The purpose of this study is to examine the level of customer satisfaction on service quality in the perception of retail banking customers in Oman. The service quality of the banks is assessed under five dimensions with 25 different attributes. The primary data were collected through a structured questionnaire from 152 respondents chosen using the 'snowball' method. The research design is quantitative and the five-dimensional SERVQUAL model was used to examine the service quality gaps between customers' expectation and perception. The effect of service quality dimensions on customer satisfaction was estimated using descriptive statistics, one sample t -tests, and correlation and regression analysis techniques. The results of the study revealed that expectation of customers was higher than their perception under all five service quality dimensions. The highest and the least service quality gap was found in the dimension of 'empathy' and 'tangibility', respectively. The findings indicate that all five service quality dimensions of the study exert a positively significant effect on customer satisfaction. In competitive environment, the banks can have a competitive edge by providing superior quality services to enhance customer satisfaction. Hence, the findings of this study will help the Omani banks to plan strategy in service delivery that leads to customer satisfaction.